CRYSTALOGRAPHIC ANALYSIS OF SOLID IBUPROFEN (CIPEEX, 2025)
In this study, we analyzed the supramolecular arrangement of an ibuprofen crystal, a widely used drug with anti-inflammatory and antipyretic properties used in the treatment of acute and chronic pain resulting from inflammatory processes, classified as a non-steroidal anti-inflammatory drug (NSAID). The molecule acts by inhibiting cyclooxygenase activity, reducing prostaglandin synthesis, and through the action of the hypothalamic thermoregulatory center. It is a first-line drug widely used as an antipyretic and pain reliever in patients of all ages, especially in premature infants with patent ductus arteriosus (Yuan et al., 2023). The compression of intermolecular interaction patterns in the supramolecular arrangement of pharmaceutical materials is essential in the context of pharmaceutical materials, as different polymorphic forms can affect physical properties such as solubility, stability, and bioavailability, as well as prevent unwanted transformations during manufacturing.
Keywords: crystallography; solid state; ibuprofen